THE ESSENCE AND SIGNIFICANCE OF LOCAL LEGAL REGULATION OF LABOUR RELATIONS IN HIGHER EDUCATION INSTITUTIONS - Bilyi, Volodymyr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: to clarify the essence and significance of local legal regulation of labour relations in higher education institutions. Research methods: formal-logical, dogmatic, comparative, and systemic-structural methods were employed. Results: the author concluded that local legal regulation of labour relations in higher education institutions constitutes autonomous legal regulation at the level of a specific higher education institution, aimed at implementing the centralized norms and adapting them to specific legal relations, considering the specificity of the subject and its needs, while respecting legislative limitations and principles of legal regulation. Discussion: despite the fact that the boundaries of local legal regulation are established at the centralized level, it has independent significance and occupies an equal position alongside centralized regulation. A significance of such regulation lies in ensuring the flexibility of legal regulation of labour relations, taking into account the peculiarities of educational activities and the implementation of the principle of autonomy of higher education institutions, however, in compliance with the principle of favourability and within the limits determined by the legislation. Local acts of a higher education institution are divided into normative (containing the local norms of law) and law-enforcement, i.e. individually determined acts of law application. They are adopted in accordance with the procedure and on the terms determined by the legislation on education and the charter of a higher education institution, taking into account specific procedural features, in particular, the role of collegial management bodies.